CHALLENGES IN ASSESSING PROCESS – MORAL AND PROFESSIONAL VALUES FROM ACQUISITION TO APPLICATION - Tascovici, Daliana; DRAGOMIR, Robert Gabriel (Annals of Spiru Haret University. Economic Series, 2017)
The present paper aims at presenting the actual situation as concern the values the students are taught about during their university courses on one hand and the necessity of the labour market on the other hand. At first, we referred to the values within the European dimension of education, as they were established by the European Commission for every state. Here we made special reference to the plan of the educational contents, as it has to contain elements of proximity and coincidence. Secondly, we talked about the new paradigms met with the educational policies. Here we stress the importance not only of knowledge, but also of competences and values the students will achieve. In order to fulfil this task, the usage of the TIC and of the educational resources opened for every type of educational contexts should be intensified. Here we also mentioned the series of activities which help the learning of the common language for a European citizenship and the defining of the new educations, adapted to the dimension of education, the European Commission and the Council of Europe propose. The next treated aspect was to establish the defining of the problem mentioned at the beginning. Here we reach the following objectives: to describe the nature of the problem, to establish the scale of the problem, to identify the affected categories, to establish the causes of the problem, to argue the need for intervention, to estimate the risks and the uncertainty of the problem discussed and also to present the healing activities. In order to get real information, we used the following methods: questionnaires (were disseminated to two different categories of respondents: students who want to get a job on one hand and employers on the other hand) and observations. The activities supposed data collecting, processing, analyzing and interpretation. In the end we draw the conclusions.